2021
DOI: 10.3138/ijfab-14.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Birthing Alone: An Ethical Analysis of Pandemic Policies Banning Birthing Partners

Abstract: During the COVID-19 pandemic, several hospitals implemented “birthing alone” policies, banning companions (e.g., partners, family members, doulas) from accompanying individuals giving birth. We offer an ethical analysis of these policies. First, we examine them through a consequentialist framework of risks and benefits. Second, we consider the significance of birth, highlighting the unique ways in which risks, relationships, and rights are understood in the context of obstetrics. We conclude that birthing alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…If patient‐centred approaches were to be emphasised in procedural learning materials, it could be presumed that the PE should be at least one priority. What we learn from their exclusion in these cases may speak to deficiencies in other fields where patient‐centeredness has been identified as imperative: patients with chronic pain, 71 disabilities 72 or terminal illness, 73 or in obstetrics, 74–76 for instance. Students have reported that patient‐centeredness needs to be more explicitly taught throughout the curriculum, 77 and undergraduate curricula have been shown to be more inclined towards ‘disease‐based perspectives’ over patient‐centred ones 78 .…”
Section: Discussionmentioning
confidence: 99%
“…If patient‐centred approaches were to be emphasised in procedural learning materials, it could be presumed that the PE should be at least one priority. What we learn from their exclusion in these cases may speak to deficiencies in other fields where patient‐centeredness has been identified as imperative: patients with chronic pain, 71 disabilities 72 or terminal illness, 73 or in obstetrics, 74–76 for instance. Students have reported that patient‐centeredness needs to be more explicitly taught throughout the curriculum, 77 and undergraduate curricula have been shown to be more inclined towards ‘disease‐based perspectives’ over patient‐centred ones 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Existing inequities in obstetric care for historically marginalized groups are also deepening, resulting in a greater likelihood of negative birth experiences and outcomes, which can lead to postpartum mental distress ( Davis et al, 2021 ; Norton et al, 2020 ; Obinna, 2021 ; Oparah et al, 2021 ). Anxieties about contagion, isolation, and quarantine, being separated from one's newborn at birth, or not being allowed birth companions during labor may be associated with a higher incidence for mothers of complications during labor and greater likelihood of medical interventions ( Friesen et al, 2021 ; Liese et al, 2021 ; Searcy and Castañeda, 2021 ). Increased episodes of obstetric violence have been reported in relation to these trends ( Sadler et al, 2020 ).…”
Section: Covid-19 and Perinatal Mental Wellbeingmentioning
confidence: 99%
“…Meanwhile, their partner had to complete the birth experience alone, which has been connected to adverse maternal and infant outcomes. 1 Although there may have been other factors that contributed to this unfortunate situation, it seems that the recording policy was a significant factor in the escalation. Policies about recording birth are contentious-hospitals and health systems are risk-averse and liability-conscious.…”
mentioning
confidence: 99%
“…Meanwhile, their partner had to complete the birth experience alone, which has been connected to adverse maternal and infant outcomes. 1…”
mentioning
confidence: 99%